Repeat Purchase intentions: Exploring the perceived values of Locally-made Hand-Woven Bags in Lagawe, Ifugao, Philippines - Client William Melchor Malinao; Sunshine D. Imapi; Felyn Tindungan; Lorena Napadawan (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Purchase behavior is a significant consideration for consumers when choosing and evaluating various products. Perceived values influencing repurchase intention are critical since these are the major inputs used by marketing managers to estimate future extra sales and develop strategies to influence consumers' repurchasing behavior. As a result, this study studied the perceived value of locally-made hand-woven bags and the repurchase intentions of consumers in Ifugao, Philippines, which also serves as the foundation for offering interventions to raise the possibility of purchasing a local product. Design/methodology/approach: The quantitative research method's descriptive-correlational research design with the use of a validated survey instrument was utilized to gather data from 202 real buyers and users of Ifugao weave bags in the three municipalities of Ifugao, namely Kiangan, Hingyon, and Lagawe. Using SPSS, data was counted, handled, and analyzed using mean, standard deviation, and Pearson-r correlation. Findings: The findings demonstrated that local weave bags have functional, experiential, cultural, aesthetics, and social values, which all influence their repurchase intention. All of the characteristics observed had a moderate to a high relationship with repurchase intent. Practical Implications: Nonetheless, marketing methods to develop Ifugao weave bags in the Philippines that integrate these criteria may have a high likelihood of success in retaining existing customers and attracting new markets.